ANALISIS PERTANDINGAN SEPAKBOLA ANTARA PSIS VS MARTAPURA FC LIGA 2 INDONESIA TAHUN 2017 (STUDY KASUS PROSES GOL PADA PERTANDINGAN PEREBUTAN PERINGKAT 3 LIGA 2 INDONESIA TAHUN 2017) - annas, amsal annas; Widodo, Achmad (Jurnal Kesehatan Olahraga, 2019)
The results of the analysis of a match is one of the factors determining the strategy of a team in competition. The results of match analysis in football can provide information about what tactics are used by the team in a match to survive, attack and find out who the key players are influential in the team.The purpose of this research is to find out the tactics and process of the goal that dominates and can win a match in the 3rd League 2 Indonesia Rankings in 2017. This research uses quantitative research with descriptive analysis method.Descriptive analysis is carried out by observing subjectively and systematically the video of the match for 3rd place in League 2 Indonesia in 2017. The results of the research and discussion that have been carried out in the previous chapter yield the conclusion that accurate passing rates and ball possession are dominant tactics and strategies that produce goals. Key: Football, Tactics, Techniques, Statistical Results.